FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN PRODUK MALAYSIA PADA MASYARAKAT KAWASAN PERBATASAN DI DESA JAGOI KECAMATAN JAGOI BABANG - Nadia, Julita; Aminuyati, Aminuyati; Syahrudin, Husni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This observe targets to determine the effect of price, product best, carrier first-class, and vicinity on buying decisions for Malaysian merchandise in Jagoi Village, Jagoi Babang District. The studies behavior using the explanatory method using a couple of linear regression. The information used is number one statistics obtained through a questionnaire. The effects of this have a look at suggest that the variables of charge, provider quality, and place have a considerable impact on shopping choices, even as variable product pleasant haven't any large impact on buying choices. hints that may be given are that enterprise owners who promote Malaysian products in border regions can maintain to improve fee competitiveness, provider excellent, and region aspects which in this look at become variables that significantly have an effect on the buying choices of border groups.